MKP1 mediates chemosensitizer effects of E1a in response to cisplatin in non-small cell lung carcinoma cells - Cimas, Francisco J. (Oncotarget, 2015)
The adenoviral gene E1a is known to enhance the antitumor effect of cisplatin, one of the cornerstones of the current cancer chemotherapy. Here we study the molecular basis of E1a mediated sensitivity to cisplatin in an experimental model of Non-small cell lung cancer. Our data show how E1a blocks the induction of autophagy triggered by cisplatin and promotes the apoptotic response in resistant cells. Interestingly, at the molecular level, we present evidences showing how the phosphatase MKP1 is a major determinant of cisplatin sensitivity and its upregulation is strictly required for the induction of chemosensitivity mediated by E1a. Indeed, E1a is almost unable to promote sensitivity in H460, in which the high expression of MKP1 remains unaffected by E1a. However, in resistant cell as H1299, H23 or H661, which display low levels of MKP1, E1a expression promotes a dramatic increase in the amount of MKP1 correlating with cisplatin sensitivity. Furthermore, effective knock down of MKP1 in H1299 E1a expressing cells restores resistance to a similar extent than parental cells. In summary, the present work reinforce the critical role of MKP1 in the cellular response to cisplatin highlighting the importance of this phosphatase in future gene therapy approach based on E1a gene.